Developing a Mathematical Literacy-Based E-Worksheet Integrating the Ciletuh Geopark for Scale and Ratio Learning - Farhah Syadidah; Sutirna Sutirna; Hanifah Nurus Sopiany (Jurnal Didactical Mathematics, 2026)
Mathematical literacy enables students to formulate, employ, and interpret mathematics in authentic situations; however, learning on scale and ratio often remains dominated by procedural instruction with limited connections to real-world contexts. This study aimed to develop a mathematics-literacy-based Electronic Student Worksheet (E-LKPD) that integrates the Ciletuh-Palabuhanratu UNESCO Global Geopark as an authentic learning environment for teaching scale and ratio in junior secondary mathematics. A Research and Development (R&D) approach employing the ADDIE model was adopted through five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants comprised expert validators, one mathematics teacher, and Grade VII students of MTs Ikhwatul Iman. Data were collected through semi-structured interviews, expert validation questionnaires, classroom observations, and student response questionnaires, and were analyzed descriptively to evaluate the feasibility and practicality of the developed instructional product. The findings indicate that the E-LKPD satisfied the predetermined criteria of feasibility and practicality, demonstrating strong instructional quality, contextual relevance, usability, and positive student acceptance during classroom implementation. The developed learning activities systematically engaged students in formulating, applying, and interpreting mathematics through authentic, context-based tasks derived from the Ciletuh Geopark, while the interactive digital environment supported structured engagement with proportional reasoning and scale concepts. These findings demonstrate that integrating authentic environmental contexts, mathematical literacy processes, and digital instructional design within a single instructional framework provides a feasible and practical approach to contextual mathematics learning. The developed E-LKPD therefore offers a pedagogically grounded digital learning resource that supports instruction oriented toward mathematical literacy in junior secondary mathematics